THE ROLE OF ISLAMIC LEADERSHIP IN IMPROVING EMPLOYEE PERFORMANCE AT THE PUTRI SARI INDAH GRESIK REST AREA KOTA BARU GRESIK - Harjanti, Wulandari; Fitrianty, Rifda; Wahjoedi, Tri; Cisilia, Magdalena (Universitas 17 Agustus 1945 Surabaya, 2024)
Objective The research in this journal focuses on Islamic leadership regarding contextual performance integrity, trust that enables employees to work well with other colleagues and be reliable in fulfilling work commitments. This is because the Islamic policies implemented and the example of a leader will make employees put their trust in the company leadership, which will make it easier for employees to cooperate and be committed to their work. Apart from indicators of trust/integrity, employee orientation also influences employee performance indicators, namely task performance. This is because clear direction regarding employee duties, both instructionally and regulatory, makes employee performance in carrying out their duties more effective and efficient. The better Islamic leadership is, the better employee performance will be. If employees work with high trust, performance will increase. Apart from that, if the superior's direction regarding employee orientation is clear, the employee's performance will be better.